Effect of nutritional intake towards Angular cheilitis of orphanage children - Rakhmayanthie, Nurdiani; Herawati, Erna; Herawati, Dewi Marhaeni Diah (Universitas Padjadjaran, 2016)
Introduction: Angular cheilitis is one of the oral manifestations of iron, vitamin B12, and folate deficiency. This manifestation frequently seen in people at first and second decade. The purpose of this study was to obtain the prevalence of angular cheilitis and its classifications related to the nutritional intake level in 6-18 years old children. Methods: This research was a descriptive study with 53 children between 6-18 years old from Muhammadiyah Orphanage Bandung as the samples. The oral cavity was examined clinically and their food consumption in a week was noted in Food Recall 24 hours and Food Frequency Questionnaire (FFQ) in order to measure their nutritional intake level. Results: There are 23 children with angular cheilitis. 13% has iron and folate deficiencies, and 87% has iron, vitamin B12, and folate deficiencies. Angular cheilitis types that has been found are Type I (39%), Type II (48%) and Type III (13%). Conclusion: The prevalence of angular cheilitis in 6-18 years old children in Muhammadiyah Orphanage Bandung was moderately high, most of them were having iron, vitamin B12, and folate deficiencies. Type II angular cheilitis was the most frequently seen.